Crystalline structures and crystallization behaviors of poly(l-lactide) in poly(l-lactide)/graphene nanosheet composites. Issue 21 (7th June 2015) - Li, Jingqing; Xiao, Peitao; Li, Hongfei; Zhang, Yao; Xue, Feifei; Luo, Baojing; Huang, Shaoyong; Shang, Yingrui; Wen, Huiying; de Claville Christiansen, Jesper; Yu, Donghong; Jiang, Shichun
<x xml:space="preserve">Abstract</x> GNS existence in PLLA favors α′ crystal formation more than α crystal formation resulting in a shift of α′–α crystal formation transition toward high Tcs.